Newborn in cardiogenic shock. Issue 6 (20th December 2017) - Wagner, Franziska; Gebauer, Roman A; Paech, Christian
Abstract : Clinical introduction: A 2-month-old baby boy was referred to our centre due to tachycardia and acute heart failure. The ECG showed a narrow complex tachycardia with a heart rate of 300 beats per minute (Figure 1 ). Echocardiographically, a patent foramen ovale and a parachute mitral valve with mild regurgitation were diagnosed; cardiac function was highly impaired. Question: Which of the following is the most likely diagnosis? Ectopic atrial tachycardia Atrial flutter Chaotic atrial tachycardia Focal micro re-entrant tachycardia Atrial fibrillation